2017
DOI: 10.1016/j.envexpbot.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Kaolin particle film application lowers oxidative damage and DNA methylation on grapevine ( Vitis vinifera L.)

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Kaolin particle film application lowers oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 63 publications
4
41
2
Order By: Relevance
“…POX and CAT convert H 2 O 2 into water and molecular oxygen, which are harmless to plants (Moller et al 2007). These results were in good harmony with the results obtained by Bernardo et al (2017). Kaolin particle film could induce SOD and CAT activities under stress.…”
Section: Antioxidant Enzymessupporting
confidence: 81%
“…POX and CAT convert H 2 O 2 into water and molecular oxygen, which are harmless to plants (Moller et al 2007). These results were in good harmony with the results obtained by Bernardo et al (2017). Kaolin particle film could induce SOD and CAT activities under stress.…”
Section: Antioxidant Enzymessupporting
confidence: 81%
“…Phenolic accumulation is also linked with several environmental disturbances (Ferrandino and Lovisolo 2014). Indeed, under high temperatures exposure, the probably increased degradation and inhibition of anthocyanins synthesis may lead to higher H 2 O 2 production with forwarding induction of the antioxidant machinery (Mori et al 2015;Conde et al 2016;Bernardo et al 2017). Flavonoids act as primary antioxidants in plant responses to a wide range of stresses, inhibiting ROS production and reducing ROS levels once they are formed (Agati et al 2012).…”
Section: Oxidative Stress and Antioxidantsmentioning
confidence: 99%
“…Many authors have focused their research on the development of environmentally friendly practices, like kaolin application, to sustain yield and quality in a challenging climate, through the reduction of leaf and fruit berry surface temperature, thus improving the antioxidant machinery (Glenn 2012;Boari et al 2015;Dinis et al 2015). In fact, foliar application of solar protectants, has already shown promising results regarding grapevine increased yield, physiological performance, and general fruit quality potential, in the context of climate change at a local scale (Coniberti et al 2013;Dinis et al 2016;Bernardo et al 2017;Dinis et al 2017;Conde et al 2018;Dinis et al 2018). Nitrogen composition in must also plays an important role on grape and wine quality potential, affecting yeast metabolism, fermentation kinetics, the amino acid content, and synthesis of volatile fermentative compounds, since the amino acids are precursors of volatile compounds (Bell and Henschke 2005;Arias-Gil et al 2007).…”
Section: Application Of Protective Compoundsmentioning
confidence: 99%
“…in viticulture are still limited. In few studies conducted in this area, it has been reported that particle films can contribute to improve berry composition and wine quality in arid regions [Brillante et al 2016, Dinis et al 2016and Bernardo et al 2017.…”
Section: Introductionmentioning
confidence: 99%